THE REPERTOUIR OF PROFESSIONAL ROLES OF SOCIAL WORKER - Котикова, О. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The article is devoted to highlighting repertoires of professional roles of social workers with the aim of further development of role approach to their preparation in universities. The author analyzes different approaches to realization of training of future social workers. The author demonstrates her own understanding of repertoires of professional roles of social workers. The results of the research allow to define professional roles of social worker, such as:»an expert», «a broker», «a manager», «a tutor», «a consultant», «a practising psychologist», «a projector»